Using A Taxonomy For Knowledge Audits: Some Field Experiences - Sharma, Ravi S.; Chia, Melvyn; Choo, Vironica; Samuel, Eyosore (Journal of Knowledge Management Practice, 2010)
The organisation of knowledge for exploitation and re-use in the modern enterprise is often a most perplexing challenge. The entire knowledge management life-cycle (for example – create, capture, organize, store, search, and transfer) is impacted by the organisation of intellectual capital into a corporate taxonomy or knowledge map (often used interchangeably). Determining the extent to which such an objective is achieved is part of the focus of what is known as a knowledge audit. In this practice-oriented article, the authors review the fundamentals of creating a taxonomy, the use of meta-data in a necessary process known as classification and the role of expertise locators where the knowledge is not explicit but resides within experts (ie. tacit knowledge). The authors conclude with a framework for conducting a knowledge audit based on the conceptual underpinnings of the corporate taxonomy. This framework is field tested in five distinct organizations for its practicability and effectiveness. It is hence the intent of the paper to provide such a useable framework for knowledge audits.